Bed‐mounted laparoscopic surgical robot system with novel positioning arm mechanism. Issue 4 (21st April 2022) - Chung, Deok Gyoon; Hwang, Minho; Cheon, Byungsik; Kong, Dukyoo; Kang, DongHoon; Lee, Dong‐Ho; Kim, Chang‐Kyun; Kim, Duksang; Han, Jung Min; Kim, Young‐Geun; Kwon, Dong‐Soo
Abstract: Background: Commercialised laparoscopic surgical robotic systems require a large operating room and can only be used in large hospitals. If the robotic system is to be used in a small‐ or medium‐sized hospital, the occupied volume must be reduced further. Methods: In this paper, we propose a bed‐mounted system that can be installed in a general operating room. Furthermore, we proposed a novel positioning arm suitable for a bed‐mounted surgical robot system. Results: The surgical possibility of the proposed bed‐mounted system has been verified. Furthermore, the surgical possibility of the proposed system was confirmed using in vivo animal experiments. Conclusions: A bed‐mounted laparoscopic robotic system and a novel positioning arm was proposed. The study's ultimate goal is to enable robotic surgery in small and medium‐sized hospitals by introducing the proposed bed‐mounted laparoscopic robot system, allowing many people to receive high‐quality medical services.